New records and range extensions of birds from Timor, Alor and Rote - Ashari, Hidayat; Prawiradilaga, Dewi M.; Eaton, James A.; Suparno, Suparno; Rheindt, Frank E. (Treubia, 2025)
The Lesser Sundas Region continues to be widely unexplored even in such relatively well-known animal groups as birds (Aves). We report the results of an ornithological expedition from November through December 2015 to Timor, Alor and Rote islands along with some opportunistic observations made in that area between 2006 to 2015, providing details on numerous first records of bird species outside their previously known geographic or elevational ranges observed or otherwise recorded during this expedition. Our results underscore the fragmentary nature of our knowledge of the composition of the avifauna of the Lesser Sunda Islands, and demonstrate that there continues to be a large volume of significant new records and range extensions of birds on these islands.